Characteristic findings of appendicular endometriosis treated with single incision laparoscopic ileocolectomy: Case report. (2020) - Hakoda, Keishi; Yoshimitsu, Masanori; Miguchi, Masashi; Kohashi, Toshihiko; Egi, Hiroyuki; Ohdan, Hideki; Hirabayashi, Naoki
Highlights: Appendicular endometriosis a rare entity which usually presents with symptoms of abdominal pain, melena, and constipation. Appendicular endometriosis can present as a submucosal tumor in the cecum without any abdominal symptoms. Single-incision laparoscopic surgery is an useful procedure for cecum tumor resection. Abstract: Introduction: We report the case of characteristic findings of appendicular endometriosis that presented as a submucosal tumor in the cecum without any abdominal symptoms treated with single-incision laparoscopic ileocolectomy. Presentation of case: The patient was a 51-year-old woman (body mass index: 21.5) who underwent an examination to investigate the cause of a positive fecal occult blood test. Her laboratory test results were normal, without anemia or tumor marker elevation. Colonoscopy revealed a submucosal tumor in the cecum. Enhanced computed tomography (CT), fluorodeoxyglucose-positron emission tomography-CT and magnetic resonance imaging failed to produce a clear diagnosis. Given the malignant potentiality of the tumor, ileocolectomy was considered potentially necessary, but she wished for minimally invasive surgery. She ultimately underwent ileocolectomy and lymphadenectomy with single-incision laparoscopic surgery. A pathological examination revealed the lesion to be appendicular endometriosis, and 14 lymph nodes with no malignancy were resected. Conclusion: Appendicular endometriosis can present as a submucosal tumor in the cecum without any abdominal symptoms. Appendicular endometriosis should be considered in the differential diagnosis of ileocecal submucosal tumor. Single-incision laparoscopic ileocolectomy was useful procedure for cecum tumor resection.